Efficacy and safety of balloon pulmonary angioplasty for residual pulmonary hypertension after pulmonary endarterectomy. (1st July 2021) - Ito, Ryosuke; Yamashita, Jun; Sasaki, Yuichi; Ikeda, Sayo; Suzuki, Shun; Murata, Naotaka; Ogino, Hitoshi; Chikamori, Taishiro
Abstract: Background: Pulmonary endarterectomy (PEA) is the standard treatment for chronic thromboembolic pulmonary hypertension (CTEPH), although some patients may experience residual pulmonary hypertension (PH). It is unclear whether balloon pulmonary angioplasty (BPA) is effective for residual PH after PEA. This study aimed to compare the BPA outcomes between patients with residual PH after PEA and those with inoperable CTEPH. Methods: This retrospective study compared BPA for residual PH after PEA (25 patients, 101 BPA sessions) and BPA alone for inoperable CTEPH (21 patients, 89 BPA sessions). All patients underwent right heart catheterisation and functional and laboratory tests before PEA or before and after BPA. Results: There was no difference in the number of BPA sessions per patient (4.0 ± 1.9 vs. 4.2 ± 1.9, p = 0.671). No significant differences were observed with respect to the mean pulmonary artery pressure (23.6 ± 9.1 vs. 21.9 ± 5.7 mmHg, p = 0.44), pulmonary vascular resistance (3.7 ± 0.5 vs. 2.8 ± 1.2 Wood units, p = 0.14), 6-min walking distance (392.1 ± 117.7 vs. 452.4 ± 90.1 m, p = 0.096), and World Health Organization functional class (I/II/III/IV: 14/11/0/0 vs. 9/12/0/0, p = 0.375). Severe haemoptysis requiring embolisation was more common in the PH after PEA group (16.0% vs. 5.4%, p = 0.018). However, no patients required mechanical ventilation or extracorporeal membrane oxygenation, and there were no procedural deaths. Conclusion: Although BPA might be effective for residual PH after PEA, it was associated with a high rate of haemoptysis. Highlights: BPA can be beneficial for residual PH after PEA. Haemoptysis tends to occur in BPA after PEA. After PEA, complications of BPA may occur even for web lesions. Due to high rates of haemoptysis, clinicians should be prepared for complications. CTEPH should be treated in a multidisciplinary manner.